2016
DOI: 10.1155/2016/6190504
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ALDH2 with Low Concentration of Ethanol Attenuates Myocardial Ischemia/Reperfusion Injury in Diabetes Rat Model

Abstract: The aim of this paper is to observe the change of mitochondrial aldehyde dehydrogenase 2 (ALDH2) when diabetes mellitus (DM) rat heart was subjected to ischemia/reperfusion (I/R) intervention and analyze its underlying mechanisms. DM rat hearts were subjected to 30 min regional ischemia and 120 min reperfusion in vitro and pretreated with ALDH2 activator ethanol (EtOH); cardiomyocyte in high glucose (HG) condition was pretreated with ALDH2 activator Alda-1. In control I/R group, myocardial tissue structure col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Furthermore, we found that daidzin (an ALDH2 antagonist) abolished baicalin‐exhibited beneficent effects against H/R‐induced cytotoxicity and apoptosis in H9c2 cells, and Alda‐1 (an ALDH2 agonist) also reversed H/R‐induced cytotoxicity and apoptosis. These results were in accordance with these studies whereby the modulation of ALDH2 activity by daidzin or Alda‐1 could affect myocardial apoptosis caused by I/R or H/R injury in isolated hearts and in cells . These results suggested that enhancing of ALDH2 activity and expression mediated H/R injury and the protective effects of baicalin against H/R injury in H9c2 cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we found that daidzin (an ALDH2 antagonist) abolished baicalin‐exhibited beneficent effects against H/R‐induced cytotoxicity and apoptosis in H9c2 cells, and Alda‐1 (an ALDH2 agonist) also reversed H/R‐induced cytotoxicity and apoptosis. These results were in accordance with these studies whereby the modulation of ALDH2 activity by daidzin or Alda‐1 could affect myocardial apoptosis caused by I/R or H/R injury in isolated hearts and in cells . These results suggested that enhancing of ALDH2 activity and expression mediated H/R injury and the protective effects of baicalin against H/R injury in H9c2 cells.…”
Section: Discussionsupporting
confidence: 91%
“…H/R, hypoxia/reoxygenation activity by daidzin or Alda-1 could affect myocardial apoptosis caused by I/R or H/R injury in isolated hearts and in cells. 24,35,36 These results suggested that enhancing of ALDH2 activity and expression mediated H/R injury and the protective effects of baicalin against H/R injury in H9c2 cells.…”
Section: Discussionmentioning
confidence: 76%
“…Chronic consumption of alcohol may lead to an increase in their activity/expression in the brain 42 . A recent study found that the cardioprotective effect of LAC is related to an upregulated ALDH2 18 . In the future, it will be important to determine the mechanisms by which LAC protects the brain against its post-ischemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the effect of alcohol consumption on cardiovascular diseases. Most studies have focused on the effects of binge drinking, however, some have sought to determine an association between light-moderate alcohol consumption and cardioprotection 17 , 18 . There have also been a limited amount of studies investigating the protective effects of low-dose alcohol on cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Diabetes is the most common reason for endstage heart disease. 3 The data from the World Health Organization (WHO) shows that about 347 million people around the world have diabetes, which is predicted to rank seventh in terms of leading death caused by the year 2030. 4 Blindness, kidney failure, as well as lower limb amputation, are demonstrated to be complications for diabetes.…”
Section: Introductionmentioning
confidence: 99%